KONSEP PENDIDIKAN AKHLAK SYEIKH MUHAMMAD SYAKIR DALAM MENJAWAB TANTANGAN PENDIDIKAN ERA DIGITAL - Syaifulloh Yusuf (Universitas Islam Sultan Agung, 2019)
This research aims to determine the values of moral education in the Kitab Washāyā Al-ābā Lil Lil Abnā ’by Sheikh Muhammad Syakir. The type of the research is library research which using an interactive model for collecting data and the data collected from primary sources and various secondary sources before presenting data. The results of this study indicate that the Kitab Washāyā Al-ābā Lil Abnā’ discusses moral education with a focus on self-glory which is divided into four important parts, namely; vertical moral values, horizontal moral values, moral values related to oneself and moral procedures. The use of language and method of delivery in this Kitab is very good. In addition, this book has a very good moral education value to further strengthen moral education in the face of the digital era.Keywords: Education, Akhlak, Digital Era, Washāyā Al-Ābā Lil Lil Abnā’